Развитие представлений о возникновении жизни на Земле - Фомина, И.Р. (Фактори експериментальної еволюції організмів, 2014)
Aims. The purpose of present brief review is to cover the development of the theory of biological evolution, mainly that its part which concerns the hypothesis of prebiotic stage of the formation of cyclic processes interconversion of inorganic and organic carbon. Results. The review presents and summarizes the literature data, reflecting the development of the Oparin’s theory since the middle of last century to the present time. Conclusions. According to modern concepts, the pathways of fixing and restoring of inorganic carbon, as well interconversion and oxidation of organic compounds have been formed at the stage of prebiotic evolution as autocatalytic processes in microscopic pores of colloidal precipitation of metal sulfides. In these pores the processes were detached from the environment by a phase interface surface with catalytic activity. Transferring of catalytic function to ribozymes and peptides, and the emergence of the genetic code was the qualitative leap between the inanimate and animate nature; and membrane formation in and around protocell and development of cell envelops determined the formation of cells as a whole organisms, their separation between the three domains: the archaea, bacteria and eukaryotes, and, most importantly, freed from the need “to live” in the pores of sedimentary rocks. Now “free-living” living systems belonged to the whole Planet!

Key words: autocatalytic processes, origin of life, prebiotic evolution.